Fatigue crack propagation of PVC-U and PVC-M in water environment - Whittle, Alan; Samat, Noorasikin; Hoffman, Mark; Burford, Robert (2008)
The addition of impact modifiers such as CPE enhance the fracture toughness to PVC to the extent that higher design stresses can be applied to PVC-M pipes compared to PVC-U. However, the fatigue response of PVC-M and PVC-U has been reported to be ostensibly the same. In this work, the fatigue crack growth mechanism has been investigated to determine why enhancement of the toughness by the impact modifier does not simultaneously increase the fatigue resistance. It was shown that both PVC-U and PVC-M exhibit a fatigue threshold. For PVC-M the threshold was more sensitive to the testing environment than was PVC-U. The fatigue crack growth rate for both materials was shown to be lower in water than in air, especially at low stress intensity factor amplitudes. Hypotheses are given for the similarities and differences between the fatigue crack growth rates of PVC-U and PVC-M and why the performance is better in water than in air.